Geneza i struktura arki Noego w „II Homilii do Księgi Rodzaju” Orygenesa w przekładzie Rufina z Akwilei - Kochanek, Piotr (In Gremium. Studies in History, Culture and Politics, 2025)
Origen presented a description of the model of Noah’s ark in his Second Homily on the Book of Genesis. This homily has been preserved in its entirety only in the Latin translation of Rufinus of Aquileia. In Origen’s opinion, the ark had a pyramidal shape with base dimensions of 90,000 x 2,500 cubits and a height of 900 cubits. It was therefore a pyramid with a rectangular base and a truncated top. The surface of this cut was a square, the side of which was only one cubit. Thanks to these dimensions, the ark not only held up well in the waves of the cataclysm, but was also able to accommodate all the animals and Noah’s family along with the food supplies they all needed. This description of the ark answered many questions from Bible readers in the early Christian era. This description was also helpful in polemics with numerous opponents who believed that the biblical pericope about the flood and Noah’s ark was just a reworked version of the Greek myth about Deucalion.